2017
DOI: 10.1098/rspb.2016.2839
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate taxa and fossils as reliable proxies of spatial biodiversity patterns in marine benthic communities

Abstract: Rigorous documentation of spatial heterogeneity (b-diversity) in presentday and preindustrial ecosystems is required to assess how marine communities respond to environmental and anthropogenic drivers. However, the overwhelming majority of contemporary and palaeontological assessments have centred on single higher taxa. To evaluate the validity of single taxa as community surrogates and palaeontological proxies, we compared macrobenthic communities and sympatric death assemblages at 52 localities in Onslow Bay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 64 publications
(103 reference statements)
0
29
0
Order By: Relevance
“…Previous research [ 3 , 5 , 83 ] has shown that large pelagic predators were decimated in tropical seas worldwide, leading to changes in functionality in the whole community. We are unaware if something like this happened to large pelagic fish in Tongoy Bay but the evidence at hand shows that mollusc communities are good surrogates for the benthic community [ 84 ], suggesting that our findings are at least a reliable representation of changes to this part of the community over time.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research [ 3 , 5 , 83 ] has shown that large pelagic predators were decimated in tropical seas worldwide, leading to changes in functionality in the whole community. We are unaware if something like this happened to large pelagic fish in Tongoy Bay but the evidence at hand shows that mollusc communities are good surrogates for the benthic community [ 84 ], suggesting that our findings are at least a reliable representation of changes to this part of the community over time.…”
Section: Discussionmentioning
confidence: 99%
“…Molluscs have a good fossil record, are common today, and are well suited for biodiversity assessments (Flessa and Jablonski 1996, Wells 1998, Bouchet et al 2002, Zuschin and Oliver 2005, Tyler and Kowalewski 2017. Molluscs have a good fossil record, are common today, and are well suited for biodiversity assessments (Flessa and Jablonski 1996, Wells 1998, Bouchet et al 2002, Zuschin and Oliver 2005, Tyler and Kowalewski 2017.…”
Section: Datamentioning
confidence: 99%
“…In addition, we assess six empirical marine data sets, four fossil and two modern, which contain (but are not limited to) species counts of molluscs. Molluscs have a good fossil record, are common today, and are well suited for biodiversity assessments (Flessa and Jablonski 1996, Wells 1998, Bouchet et al 2002, Zuschin and Oliver 2005, Tyler and Kowalewski 2017. The empirical data sets also cover a large range of ecological indices, although not as extreme as the simulated data (Table 2).…”
Section: Datamentioning
confidence: 99%
“…The current dataset should prove useful in understanding processes that influence biodiversity on multiple scales, and in developing effective strategies for conservation and coastal resource management 3 , 30 , 31 . The dataset described herein was collected in conjunction with sympatric death assemblage data 32 , 33 , for a project aimed at examining higher taxonomic fidelity of death assemblages (i.e., the incipient fossil record). Quantitative analyses of paleontological fidelity, based on comparisons of living communities to sympatric death assemblages, is an important research direction in paleobiology.…”
Section: Background and Summarymentioning
confidence: 99%
“…Quantitative analyses of paleontological fidelity, based on comparisons of living communities to sympatric death assemblages, is an important research direction in paleobiology. To augment previous research, which has focused on single higher taxa (primarily mollusks), a comparative fidelity analyses across multiple groups of marine macrobenthos was carried out recently 32 , 33 . Using coastal and shallow subtidal settings of the Outer Banks (North Carolina, U.S.A.), fidelity and relative fossilization potential of multiple paleontologically important marine macro-invertebrate groups were assessed.…”
Section: Background and Summarymentioning
confidence: 99%